Prevalence survey of nosocomial infections in the Inner Mongolia Autonomous Region of China [2012-2014] - Liu, Wei-Ping (J Thorac Dis, 2015)
BACKGROUND: To investigate the prevalence of nosocomial infections, the distribution of nosocomial infection sites, the use of antibiotic and the situation of detected nosocomial infection pathogens in the Inner Mongolia Autonomous Region of China from 2012 to 2014, to grasp the current conditions of regional nosocomial infections in timely, for the development of infection prevention and control measures to provide a basis for effective hospital. METHODS: A survey of the prevalence of nosocomial infections was conducted in target hospitals using the combination of a bedside survey and medical record review. RESULTS: In total, 101,907 inpatients were surveyed from 2012 to 2014. There were 1,997 cases of nosocomial infections, accounting for an average prevalence of 1.96%. The infection site was mainly the lower respiratory tract. Higher prevalence of nosocomial infections occurred in the comprehensive intensive care unit (ICU), Neurosurgery Department, and Hematology Department. The average rate of antibiotic use was 33.72%, and the average submission rate for bacterial cultures for patients who received therapeutic treatment with antibiotics was 28.26%. The most common pathogens associated with nosocomial infections were Gram-negative (G(−)) bacteria, and frequently detected bacterial pathogens included Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii, and Staphylococcus aureus. CONCLUSIONS: The survey of the prevalence of nosocomial infections helped to identify problems in the control process of nosocomial infections and to develop targeted measures for the prevention and control of these infections accordingly.